Climate change variability adaptation and farmers decisions of farm exit and survival in Pakistan - Irshad Ahmad, M.; Ma, H.; Shen, Q.; Rehman, A.; Oxley, Leslie (2024)
Pakistan is listed among the countries that are extremely vulnerable to climate changes and it has experienced several climatic and natural disaster shocks with adverse impacts on its agricultural sector and farmers livelihoods. This study investigates adaptation to climate change as a means of farm survival and farm exit in Pakistan by using panel datasets and empirically employs Multinomial Logit Model (MLN) and the Theory of Planned Behavior (TPB). The results reveal, first, farm experience significantly increases the likelihood of climate change adaptation and decreases the likelihood of farm exit. Second, land and livestock ownership both have positive and significant impact on farm survival with adaptation strategies and decrease the probability of farm exit. Third, climatic disasters have positive and significant impact on farm exit. Four, extension services have negative and significant impact on adaptation strategies and increase the probability of farm exit for those farms who did not receive climate change adaptation strategies information timely. Finally, TPB results illustrate that non-adapters climate change future intensions are affected by attitude, perceived behavioral control and subjective norms. The study findings bring scholars and policymakers attentions towards next level of climate change impact on farm exit, and are useful for farm survival and recruiting new farmers by promoting mixed-crop livestock production systems in the face of climate change, and during viral diseases such as Lumpy Skin Disease (LSD) of animals that caused a large number of animals deaths nationally and internationally.